2021
DOI: 10.1111/ejh.13708
|View full text |Cite
|
Sign up to set email alerts
|

A low‐dose rituximab regimen for first‐line treatment of acquired haemophilia A

Abstract: Novelty statement:1. What is the new aspect of your work?• Acquired haemophilia A (AHA) typically occurs in elderly patients with multiple comorbidities. Immunosuppression has demonstrated improved overall survival and remission rates; however, treatment-related complications in this cohort often occur. Efficacious but dose-reduced immunosuppression for this rare condition will hopefully reduce morbidity and is an important area for further research. What is the central finding of your work?• Universal immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Various definitions of remission in previous AHA studies and the crossover design in our study may contribute to these results 9 . There are case reports on reduced‐dose RTX regimen showing good efficacy 11–15 . They also showed no serious AEs, especially no severe infection.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Various definitions of remission in previous AHA studies and the crossover design in our study may contribute to these results 9 . There are case reports on reduced‐dose RTX regimen showing good efficacy 11–15 . They also showed no serious AEs, especially no severe infection.…”
Section: Discussionmentioning
confidence: 72%
“…9 There are case reports on reduced-dose RTX regimen showing good efficacy. [11][12][13][14][15] They also showed no serious AEs, especially no severe infection. Complete B-cell depletion was also observed in our study nearly 1 or 2 weeks after RTX administration, demonstrating the efficacy of our single-dose RTX in B-cell depletion.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Our results are comparable to those of the recent randomized open non inferiority trial which showed similar efficacy and safety of a single dose of RTX [24 (77.4 %) patients in the rituximab group and 22 (68.8 %) in the cyclophosphamide group achieved CR within 8 weeks. However, patients were younger (42 [31,59] for the single-dose rituximab group and 55 [34,67] for the cyclophosphamide group), and an autoimmune disease was the most common underlying disease in both groups [23].…”
Section: Discussionmentioning
confidence: 99%